2017
DOI: 10.1186/s40623-017-0637-z
|View full text |Cite
|
Sign up to set email alerts
|

Planetesimal formation by an axisymmetric radial bump of the column density of the gas in a protoplanetary disk

Abstract: We investigate the effect of a radial pressure bump in a protoplanetary disk on planetesimal formation. We performed the two-dimensional numerical simulation of the dynamical interaction of solid particles and gas with an initially defined pressure bump under the assumption of axisymmetry. The aim of this work is to elucidate the effects of the stellar vertical gravity that were omitted in a previous study. Our results are very different from the previous study, which omitted the vertical gravity. Because dust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Some key limitations of this work include the omission of stellar vertical gravity, particle self-gravity, and an azimuthal component to the simulations. Onishi & Sekiya (2017) corrected the first problem with a new 2D simulation that included vertical gravity. Because they allow dust particles to sediment, they found that the back-reaction is only a significant force in the thin dust layer at the midplane, where the particle density is high, and the majority of the pressure bump is largely unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…Some key limitations of this work include the omission of stellar vertical gravity, particle self-gravity, and an azimuthal component to the simulations. Onishi & Sekiya (2017) corrected the first problem with a new 2D simulation that included vertical gravity. Because they allow dust particles to sediment, they found that the back-reaction is only a significant force in the thin dust layer at the midplane, where the particle density is high, and the majority of the pressure bump is largely unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works that investigated the evolution of dust in the vicinity of a pressure bump ( Taki et al (2016); Onishi and Sekiya (2017); Huang et al (2020); Carrera et al (021a)) did not report unstable behavior of dust rings that formed at a pressure bump, as described in the previous sections. Although Taki et al (2016) found that the pressure bump gets destroyed by the particle feedback within hundreds of orbital periods without sufficient reforcing, this turned out to be caused by the neglect of vertical stellar gravity and hence dust sedimentation in the midplane (Onishi and Sekiya 2017). Also, for the parameters used by Taki et al (2016) (Z = 0.1, τ 0 = 1) or Huang et al (2020) Fig.…”
Section: Discussionmentioning
confidence: 68%
“…One therefore assumes that additional processes are required to trigger the SI. Among these processes are particle concentration in zonal flows (Johansen et al 009b), pressure bumps (Haghighipour and Boss 003a,b;Taki et al 2016;Onishi and Sekiya 2017;Huang et al 2020), vortices (Barge andSommeria 1995;Johansen et al 2004;Klahr and Bodenheimer 2006;Fu et al 2014;Crnkovic-Rubsamen et al 2015;Raettig et al 2015;Miranda et al 2017;Surville and Mayer 2019), or other instabilities such as the Dust Settling Instability (DSI: Squire and Hopkins (2018); Krapp et al (2020)).…”
Section: Introductionmentioning
confidence: 99%
“…This is still justified since our particles are too small (St < 10 −3 ) to cause any perturbation beyond slowing down the concentration process and we can be infer it also by studying the single dust species scenario described in the Appendix A.1. Studies of Onishi & Sekiya (2017) also showed that the back-reaction still allows the dust to accumulate at pressure maxima, and that the dust traps do not self-destruct by this effect when taking into account the vertical distribution of solids. For the reactivation phase we implement the gas velocities as described by equations Eq.…”
Section: Simulation With Dust Back-reactionmentioning
confidence: 99%